Mathematical models for tar cracking and char reactions in a bubbling fluidised bed reactor - Ahmed, Abdulmajeed Mohammed Al-Ogaidi (2019)
Tar is a contaminant product produced from the devolatilisation of the biomass in the gasification process which consists of a collection of organic compounds. The formation of tar depends on the gasifier setup and operating conditions, and can cause blockage in downstream equipment and facilities. Therefore, it is essential to reduce its levels through examining the effects of the parameters on its formation. In this research, two separate models were built to represent devolatilisation stage in the upper part and fluidized-bed stage in the down part of a lab-scale fluidized-bed gasifier of top feeding configuration. The upper part of the reactor was modelled using a pseudo-equilibrium model (PEM) which employed yield correlations for tar, bio-oil, char, gas composition, and CH4 obtained from experimental work at temperature range of 650 – 850ºC. Two parameters were investigated: temperature (650 – 850ºC) and carrier gas flow rate (10 – 30 L/min). The results showed a good prediction for tar yield with low root mean square (RMS = 0.003) compared to experiments, and conversion (59.7%) compared to experiments (51.5%) at 850 ºC. The change of flow rate showed slightly increase of tar yield. Fair predictions obtained for other products. The down part of the reactor was modelled for the gasification reactions of char using two-phase model. The char diffusion equation was imposed in the model to estimate the carbon conversion and oxygen consumption. Moreover, the effects of two parameters on char reactions were investigated: temperature (650 – 850ºC) and equivalence ratio (ER) (0.2 – 0.4). The results showed that carbon conversion, oxygen consumption and final tar yield were 33 wt%, 66 vol.%, and 5 g/Nm3, respectively. Meanwhile, the yield of CO increased progressively while CO2 increased considerably when temperature increased. The change of ER (0.2 – 0.4) decreased the yield of CO and CO2. The temperature has a major effect on the tar yield and conversion in the upper part of the reactor. Meanwhile, the implication of a correction factor for steam reforming reaction (SRMR) in the PEM is important for better predictions of the yield of CO and CH4 produced from the devolatilisation. On the other hand, the high location of the feeding point reduces the carbon conversion and oxygen consumption, and decouples the reactions of tar with O2 and CO2 which consequently reduce the yield of H2 and CO.